Quality Of School Education From Various Studies of Expert - Wahyudin Wahyudin; Kok Shiong Pong (Indonesian Journal of Education (INJOE), 2021)
The quality of education in various schools is inseparable from challenges and opportunities. Challenge is a competition between one school and another. Meanwhile, opportunity cannot be separated from the efforts of every leader who wants change so that it cannot be separated from various styles of leadership.